2018
DOI: 10.3889/oamjms.2018.218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Clinical Proficiency of RDTs, Microscopy and Nested PCR in the Diagnosis of Symptomatic Malaria in Ilorin, North-Central, Nigeria

Abstract: BACKGROUND:Accurate laboratory diagnosis of suspected malaria is the hallmark to the control of the disease.AIM:The clinical proficiency of commercial Rapid Diagnostic test kits (RDTs) using nested PCR as quality control was evaluated among patients attending two public healthcare providing institutions in Ilorin, Kwara state, North-Central, Nigeria.METHOD:A cross-sectional evaluation of finger prick blood samples of volunteer patients were accessed for malaria parasites with pLDH, HRP2, Pf, Pf/PAN and nested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
(76 reference statements)
0
6
1
Order By: Relevance
“…The scores of the identification of P. vivax and P. ovale were quite low; the positive predictive value was only 51.60 and 28.95%. Morphological identification of P. vivax and P. ovale by microscopy has always been difficult, and requires rich experience and technical training from the technician ( 26 , 27 ). That's why, in this study, there were many misjudgments in the identification between the two.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scores of the identification of P. vivax and P. ovale were quite low; the positive predictive value was only 51.60 and 28.95%. Morphological identification of P. vivax and P. ovale by microscopy has always been difficult, and requires rich experience and technical training from the technician ( 26 , 27 ). That's why, in this study, there were many misjudgments in the identification between the two.…”
Section: Discussionmentioning
confidence: 99%
“…The study also found that older technicians scored lower. Under normal circumstances, the technician's competency of plasmodium microscopy will increase with age; rich microscopy experience leads to better competence ( 13 , 26 , 35 ). However, there were no local malaria cases reported in Chongqing from 2011, and there were only about 30 imported cases each year in last decade.…”
Section: Discussionmentioning
confidence: 99%
“…In order to employ them for the nested PCR, already-existing primers that target the 18S rRNA of Plasmodium species were changed in cycling conditions (nPCR). Isolated gDNA and the primary amplicon, respectively, were employed for the PCR amplification in the primary and nested PCRs [15].The highly sensitive nested PCR is commonly used for microscopy accuracy assessment, epidemiological research, diagnosis confirmation, and pharmaceutical efficacy evaluation. The high cost, complexity, material requirements, and strenuous exercise requirements of nPCR techniques may prevent many resource-poor populations from finding them to be a suitable diagnostic tool [14].…”
Section: Nested Pcr (Npcr)mentioning
confidence: 99%
“…However, in locations with limited resources, such tools are not readily available, and in endemic populations, the need for a skilled technician, quality control, and equipment maintenance may be "far-reached." It is concerning to see that qPCR has a high proportion of false positive results [15].…”
Section: Quantitative Pcr (Qpcr)mentioning
confidence: 99%
“…Other studies obtained in Nigeria had obtained different sensitivity and specificity. Ogbolu and others obtained a sensitivity and specificity of 29.4% and 100% in a study in Ile-Ife[27] in south western Nigeria, Kanyi and others 53.8% and 100% in Lagos [28] and Waggoner et al obtained 97.1% and 93.5% also in Lagos[39]. It has been estimated that a diagnostic test with 95% sensitivity and 95% specificity requiring minimal infrastructure would avert more than 100,000 deaths and about 400 million unnecessary treatments[40].…”
mentioning
confidence: 99%